Operating System and Server Integration for Business Effectiveness - Apriani, Desy; Afrijaldi, Rizki; Auliya, Nur; Darmawan, Aden Andre (Pandawan Sejahtera Indonesia, 2024)
Management Information Systems (MIS) have a crucial role in supporting the effectiveness of a company or agency. A strong MIS ensures optimal internal planning and control, involving people, documents, technology and procedures. The importance of MIS demands synergistic integration between the operating system and servers to manage hardware resources and store information efficiently. This research aims to explore the factors that influence SIM in the context of operating system and server integration. The focus is on understanding the impact of this integration on business effectiveness, particularly in terms of planning, control and data storage. Research reveals that the integration of operating systems and servers positively contributes to increasing SIM effectiveness. Harmonious cooperation between the operating system and servers encourages optimization of hardware resource management and information storage, supporting more efficient internal planning and control. These findings provide a new view regarding the importance of operating system and server integration in optimizing SIM. The implementation of this integration is expected to improve business performance through more accurate planning, tight control and efficient data storage. The novelty of this research lies in the integrative approach to operating systems and servers in the context of SIM. A deeper understanding of these relationships can provide practical guidance for companies to improve the effectiveness of their information systems.